2020
DOI: 10.3390/cancers12051204
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Artificial Intelligence to Prostate Multiparametric MRI (mpMRI): Current and Emerging Trends

Abstract: Prostate carcinoma is one of the most prevalent cancers worldwide. Multiparametric magnetic resonance imaging (mpMRI) is a non-invasive tool that can improve prostate lesion detection, classification, and volume quantification. Machine learning (ML), a branch of artificial intelligence, can rapidly and accurately analyze mpMRI images. ML could provide better standardization and consistency in identifying prostate lesions and enhance prostate carcinoma management. This review summarizes ML applications to prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 109 publications
(161 reference statements)
0
35
0
Order By: Relevance
“…Additional work in this dataset should progress beyond prostate segmentation and detect prostate lesions. Lesion identification is a much more challenging task for AI and data augmentation with a generative adversarial network (GAN) [36] could be very useful since this technical problem lacks sufficient training data [37].…”
Section: Discussionmentioning
confidence: 99%
“…Additional work in this dataset should progress beyond prostate segmentation and detect prostate lesions. Lesion identification is a much more challenging task for AI and data augmentation with a generative adversarial network (GAN) [36] could be very useful since this technical problem lacks sufficient training data [37].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis based on mpMRI suffers from interobserver variability, influenced by experience [ 76 ], and subtleties in differentiating benign and premalignant lesions that may closely resemble PCa [ 77 ]. Studies of AI-based radiomics have suggested that these models may become a reliable and informative biomarker complementary to human interpretation of mpMRI [ 23 , 24 , 31 ].…”
Section: Multiparametric Mri (Mpmri) Of Prostate Cancermentioning
confidence: 99%
“…The growing interest in AI techniques and their applications in medicine [ 30 ], has carried over to computer-aided diagnostic (CAD) systems to detect, grade, and introduce other classifications of PCa [ 31 , 32 , 33 , 34 , 35 , 36 ]. So far, the term of radiomic with AI represents the features extraction and interpretation of hidden quantitative imaging data to be used for CAD [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urological Cancer 2020 contains three reviews [ 31 , 32 , 33 ] and seven articles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ] about prostate cancer. Sarkar et al [ 31 ] reviewed the intimate mechanisms of angiogenesis in prostate cancer and their possible blockade to maximize benefits minimizing toxicity.…”
mentioning
confidence: 99%
“…In this sense, a recent study showed that PTEN heterozygosity in LKB1 -mutant mice promotes the development of a metastatic aggressive form of prostate cancer [ 41 ]. Bardis et al [ 33 ] reviewed the applications of Artificial Intelligence to multiparametric magnetic resonance imaging in prostate cancer and its interaction with radiologists’ algorithms.…”
mentioning
confidence: 99%